Not a new problem: violence in the lives of disabled women - Owen, Michelle; Ristock, Janice L.; Hiebert-Murphy, Diane; Ternette, Emily (Understanding violence series, 2018)
"Violence in the lives of women with disabilities is not a new problem, but it is a problem about which little has been written. This gap in our knowledge needs to be addressed, as women with disabilities are valuable members of our society whose experiences need to be made known. Without such knowledge, political action for social justice and for the prevention of violence is impossible. Contributors to Not a New Problem examine the experiences of Canadian women with disabilities, the need for improved access to services and the ways this violence is exacerbated by and intersects with gender, sexuality, indigeneity, race, ethnicity and class"--